Mengungkap Human Capital di Indonesia, Singapura dan Timor Leste Menurut World Bank Group - Triansyah, Fadli Agus; Rahayu, Sri; Aisyah, Iis; Dahlan, Dadang (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to reveal and compare the level of human capital in Indonesia, Singapore and Timor Leste using the Human Capital Index (HCI) developed by the World Bank Group. The method used is a literature study with a qualitative approach, analyzing various secondary data sources, including official World Bank reports. This research focuses on the main components of the HCI, namely the quality of education, healthy life expectancy, and future productivity potential. The analysis shows that Singapore has the highest HCI score, followed by Indonesia and Timor Leste. Singapore excels in every indicator, such as child survival probability, expected number of years of schooling, and harmonized test scores. Indonesia, although better than Timor Leste, still has significant gaps in education and health quality compared to Singapore. These findings highlight the importance of increasing investment in the education and health sectors in Indonesia and Timor Leste to improve human capital that can support sustainable economic growth.